Soluble antigens in plasma allow mismatched transfusion without hemolysis. Issue 4 (1st February 2018) - Sikora, James; Gregory, Jason; George, Alan; Clayton, Simon; Zou, Baiming; Robinson, Matthew; Mukhtar, Faisal; Pelletier, Joseph P.
Abstract : BACKGROUND: Universal plasma is a scarce resource when a massive transfusion protocol has been initiated. Previous studies have reported success using group A plasma in place of the universal plasma, group AB. It is unclear why there are not more reports of hemolytic reactions occurring from this practice. One possible explanation is the presence of water‐soluble antigens in the patient plasma that bind to, and neutralize, the soluble antibodies present in the transfused plasma. STUDY DESIGN AND METHODS: Expired units of plasma were used to make dilutions that consisted of mixtures of group A and B plasma and saline. Serial dilutions of these samples were performed starting from undiluted up to 1024. The dilutions were titrated using a group B red blood cell preparation. The titrations were read after incubation. RESULTS: The titers that resulted from the mixed plasma dilutions were significantly lower or showed no agglutination when compared to the group A–specific saline dilutions. The differences between the saline dilutions and mixed group dilutions were significant (p < 0.001). CONCLUSION: Our study shows that secretor status would provide protection from isoantibodies. The dissolved B antigens in the group B plasma absorb and/or bind to the group B isoantibodies in the group A plasma. This mechanism gives a protective effect against hemolytic reactions in massive transfusion situations in the trauma setting when group A plasma is used instead of group AB plasma. This protective effect is revealed with the paucity of intravascular hemolysis observed in these out‐of‐group massive transfusions.